AN ANALYSIS OF EFFECTIVE METHODS FOR TEACHING ENGLISH PRONUNCIATION TO NON NATIVE SPEAKERS - Fusvita Sari (Journal of English Education, 2025)
This study aims to analyze effective methods for teaching English pronunciation to non-native speakers, addressing the challenges they face in mastering the phonetic nuances of the language. With the increasing globalization and the necessity for effective communication in English, the importance of pronunciation cannot be overstated. This research reviews various instructional strategies, including phonetic training, the use of technology-enhanced learning tools, and interactive speaking practices. A mixed-methods approach was employed, incorporating both qualitative and quantitative data collected from language learners and instructors across diverse educational settings. The findings indicate that a combination of traditional phonetic instruction and modern technological tools, such as mobile applications and online resources, significantly enhances learners' pronunciation skills. Additionally, the study highlights the effectiveness of immersive practices, such as shadowing and peer feedback, in fostering a supportive learning environment. The results suggest that tailored pronunciation instruction, which considers individual learner needs and preferences, leads to improved outcomes in pronunciation proficiency. This analysis contributes to the field of language education by providing insights into effective pedagogical approaches for teaching English pronunciation to non-native speaker.